Assurance in corporate sustainability reporting in the United Kingdom: stakeholder and corporate perspectives - Pinilla-Urzola, Angela (2011)
Sustainability assurance is developing rapidly in the United Kingdom, despite a negative stance from management. Previous studies have examined the practice as represented in statements from 2001 to 2004, companies’ reasons for commissioning assurance services, and the views of assurance providers on stakeholder-centred practice. Despite the importance of stakeholder participation within sustainability assurance exercises, far too little attention has been paid to stakeholders and their views on the phenomenon of sustainability assurance. This research identifies the trends and emerging issues in the practice between 2001 and 2007, investigates corporate management’ views on those issues, and examines stakeholders’ perspectives on the potentialities and problems of assurance practice.